Sales Process Automation in the Client’s Management Context trough CRM - Brambilla, Flávio Régio (Revista de Administração da UFSM, 2012)
In the management of customers’ relationships or Customer Relationship Management (CRM), the Sales Force Automation (SFA), or automation of the sellers, evoke a significant impact in technological as in relational side. Trough a Case Study in the relationship between a developer company and other company as user of CRM, results indicate that, contrary to the theory, the automation not always is noticed by the personnel of sales as a threat, but as a supporting tool. It is supposed that the technological readiness of the organizations exercises impact to obtaining contrary results in front of the general theoretical propositions.